PENGARUH TRANSISI DEMOGRAFI TERHADAP KEMISKINAN - Stephani Febryanna (Syiah Kuala University, 2022)
Various studies have been conducted to create policies that can reduce poverty rates, and several researchers have tried to look at the role of demography on poverty. One of them is discussing the relationship between components of demographic variables in Indonesia; cross-national regression shows that high fertility rates increase poverty by slowing economic growth. Combined fertility and mortality are associated with reduced fertility and mortality rates that simultaneously produce changes in population growth as a model of the demographic transition. Indonesia has almost completed this first demographic transition even in several provinces and districts, has passed the first demographic transition and is currently in the second demographic transition phase. Secondary data is macro, in the form of Indonesian time series data sourced from the World Bank, and is annual data, namely 1998-2019. An interesting relationship between the dependency ratio and the poverty rate is related to the term jobless growth, the more working-age, the more jobs are needed, but if there are not many jobs, unemployment will increase even though the economic growth is quite good.